Characterization for verification of electrostatic generator's effectiveness for power generation - Motakabber, S. M. A.; Zahirul Alam, A. H. M.; Ibrahimy, Muhammad Ibn; Za'bah, Nor Farahidah; Sidek, Khairul Azami (International Islamic University Malaysia, 2018)
Gradually usages of electric power are increasing in every country due to its easy transmission, distribution and management. Definitely, a small enhancement of the efficiency in this system will change the economy of the country. Now, electromagnetic induction is used to generate the electric power and most of the cases it is AC supply. However, electrostatic induction can also be used to generate the electric power; but the drawback of this system is, it can generate power in high voltage DC (HVDC) supply only. Another unruly matter is, the HVDC can easily damage the conducting material due to high voltage electrical arc discharging and break down the insulation materials. The challenging task of this research is to find a suitable and sustainable system to transform the HVDC into AC supply. Tremendous progress of the material science and electronic devices make it easy to convert the electric power supply from the DC to AC using inverters and switching circuits. Once the electric power supply converted into AC from the DC, the next steps are as usual and it does not need to modify the existing electrical system anymore. The magnetic and electric fields are different in nature, thus their field drags are also different. Moreover, the magnetic induction type generator is heavier, therefore, it imposes large force of static inertia and frictional loss compared to the electrostatic generator. The research is to characterize, study the HVDC inverter, examine the electric power generation efficiency of the electrostatic generator. It is also to carry out a texts survey to find out the scope of uses of the electrostatic generator and HVDC in Malaysia based on the characterization and efficiency of the electrostatic generator. Consequently, a simple, high efficiency and low cost as well as an economic electric power generation are expected to achieve. A large amount of energy is used directly in the form of electric power in every country around the world, due to its easy transmission, distribution and management. Moreover, it is environment friendly. Undoubtedly, a small amount improvement of efficiency in this system can radically change the economy of the world. Nowadays, electromagnetic induction is used to generate the electric power and most of the cases it is in the form of alternating current (AC). However, electrostatic induction can also be used to generate the electric power, but the drawback of this system is, it can generate the power in the form of direct current (DC) only. As a result, it uses are limited within some special applications and research only. It is possible to overcome this shortcoming of the system by converting the DC into AC supply. Another unruly matter is, the high voltage can easily damage the conducting material due to high voltage electrical arc discharge and break down the insulation materials. As a result, to make a sustainable system it needs special materials and equipment. Now, there is a tremendous progress of the material science and electronic devices that make it easy to convert the electric power supply from the DC to AC or vice versa. Therefore, electric power can easily be controlled with the aid of electronic circuits. Once the electric power supply converted into AC from the DC which is generated from the electrostatic generator, the next steps are as usual and it is no longer needed to modify the existing electrical system. However, the challenging task of this research is to find a suitable and sustainable system to transform the DC high voltage into AC supply. Since, the magnetic and electric fields are different in nature, their fields drag are also different. Moreover, the magnetic induction type generator is heavier than the electrostatic generator, as a result, the magnetic induction type generator imposes large force of static inertia and frictional loss compare to the electrostatic generator. The aims of this research are to characterize the electrostatic induction generator, to study the high voltage DC to AC inverter for electrostatic induction type generator, to examine the electric power generation efficiency of the electromagnetic induction and electrostatic induction type generators. It is also to carry out a text survey to propose the scope of uses of the electrostatic generator and HVDC in Malaysia based on the characterization and efficiency of the electrostatic generator obtained.